It's a perfect day - Pizer, Abigail (Glenview, ıllinois : Scott Foresman, 1990)
A rooster, a pig, a cow, and many other farm animals enjoy a perfect day in the country. Uses rebuses.
"Celebrate reading! Scott Foresman 1A"--Cover.
1.9
K-3.
K-3
Keywords: Readers (Elementary).; Day -- Fiction; Domestic animals -- Fiction; Day -- Fiction; Domestic animals -- Fiction; Rebuses; Riddles